Reproductive function after radioactive iodine treatment for differentiated thyroid carcinoma patients: a systematic review - Elliyanti, Aisyah; Aziza, Zulva; Kurniawati, Yulia; Khambri, Daan; Amir, Arni; Katar, Yusticia (Medical Journal of Indonesia, 2025)
BACKGROUND Thyroid cancer is one of the most prevalent cancers in the endocrine system, with a rapidly rising incidence over the past 3 decades. Treatment for patients with differentiated thyroid cancer (DTC) typically includes surgery, radioactive iodine (I-131) therapy, and levothyroxine (L-T4) suppressive therapy. This study aimed to explore the potential side effects of I-131 therapy on reproductive function in men and women with DTC. METHODS A literature search was performed using 4 databases (PubMed, ScienceDirect, BioMed Central, and Google Scholar), limited to English publications since 2013. Clinical trials and observational studies that evaluated I-131 in DTC, focused on reproductive-age patients, and included pre-therapy or during-therapy examinations, administered doses, and treatment frequencies of I-131 were selected. The Joanna Briggs Institute Critical Appraisal Checklist is used as a comprehensive evaluation tool, and the literature quality was categorized as high, moderate, and low. RESULTS The final 17 articles examined the effect of I-131, with 13 focusing on women's reproductive function and 4 on men's. Women who received I-131 therapy can lower anti-Mullerian hormone levels and disrupt menstrual cycles within the first year, and it does not affect subsequent pregnancies. For men, the therapy led to elevated levels of follicle-stimulating hormone and luteinizing hormone, along with changes in sperm quantity, morphology, and motility, which tend to normalize within a year post-therapy. CONCLUSIONS The reproductive side effects associated with I-131 therapy are generally transient, with most individuals experiencing a return to normal within 1 year following treatment.